menghubungkan Menghubungkan Islam dan Sains: Langkah Menuju Kemajuan Ilmu Pengetahuan - sari, laily vicha (Maliki Interdisciplinary Journal, 2025)
In recent decades, the importance of integrating science and religion has been increasingly emphasized. This article discusses the integration of the relationship between science and Islam in the development of science. At first glance, science and Islam seem like two opposing fields. However, with the right approach, both can complement each other and contribute significantly to the development of science. Integrating the relationship between science and Islam requires combining scientific principles with Islamic values and teachings. Applying scientific principles such as scientific methods, objective research, and critical thinking in an Islamic context can deepen our understanding of the universe and its creation. In the development of science, the integration of the relationship between science and Islam plays an important role. Much scientific research conducted by Muslim scientists has made important contributions in various fields such as mathematics, astronomy, medicine and philosophy. This integration also fosters collaboration between scientists and academics, allowing them to learn and expand each other’s knowledge. On the other hand, Islamic teachings can provide a moral and ethical framework for the practice of science. Islam teaches the need to maintain balance and justice in the use of knowledge and maintain harmony between humans and nature. By combining science and Islamic perspectives, we can gain deeper insight into life and our purpose in this world.